OVERVIEW OF KNOWLEDGE OF HALITOSIS AMONG EMPLOYEES IN FACULTY OF DENTISTRY, MOESTOPO UNIVERSITY - Yuditha, Solva; Kusparmanto, Lukas; Maharani, Hairunisza Putri (Universitas prof. Dr. Moestopo (Beragama), 2023)
Background: Halitosis is an unpleasant mouth odor exhaled during breathing. Approximately 80% of halitosis can originate from the oral cavity, while about 10-20% may arise from sources outside the oral cavity. Halitosis has psychological impacts on individuals, leading to poor social communication and reduced social activities. Objective: To assess the overview of knowledge and information regarding halitosis among employees in the environment of Faculty of Dentistry, Moestopo University. Methods: This study employs a descriptive research design with a cross-sectional approach. The sampling technique employed is Purposive sampling, the sample size consists of 58 respondents who participated in the study through a questionnaire distributed using Google Forms and paper-based formats, consisting of 15 closed-ended questions. Respondents’ knowledge is categorized into three levels: good, fair, and poor. Results: Based on the distributed questionnaires, 30 respondents (51.7%) demonstrated good knowledge, 18 respondents (31%) had fair knowledge, and 10 respondents (17.2%) exhibited poor knowledge of halitosis. Conclusion: the analysis data concerning the overview of halitosis knowledge among employees in the environment of Faculty of Dentistry, Moestopo University, it can be concluded that the knowledge of halitosis among employees in the Faculty of Dentistry, Moestopo University environment is categorized as good, with a percentage (51.7%).